2020
DOI: 10.1007/s00431-020-03584-w
|View full text |Cite
|
Sign up to set email alerts
|

Proportional assist ventilation (PAV) versus neurally adjusted ventilator assist (NAVA): effect on oxygenation in infants with evolving or established bronchopulmonary dysplasia

Abstract: Both proportional assist ventilation (PAV) and neurally adjusted ventilatory assist (NAVA) provide pressure support synchronised throughout the respiratory cycle proportional to the patient's respiratory demand. Our aim was to compare the effect of these two modes on oxygenation in infants with evolving or established bronchopulmonary dysplasia. Two-hour periods of PAVand NAVA were delivered in random order to 18 infants born less than 32 weeks of gestation. Quasi oxygenation indices ("OI") and alveolararteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
0
20
0
1
Order By: Relevance
“… 107 Hunt et al similarly compared NAVA and proportional assist ventilation in 18 infants born <32 weeks of gestation with evolving or established BPD and reported that there was no significant difference in the mean oxygenation index between the two modes, but the mean alveolar–arterial gradient was better on NAVA. 108 NAVA can also be used as a non-invasive modality. Forty infants with a gestational age of 28–36 weeks requiring CPAP for respiratory distress were randomised to non-invasive NAVA or CPAP and the authors reported that, after 12 h of treatment, the mean FiO 2 requirement and need for invasive ventilation did not differ between the two groups.…”
Section: Neurally Adjusted Ventilator Assist (Nava)mentioning
confidence: 99%
“… 107 Hunt et al similarly compared NAVA and proportional assist ventilation in 18 infants born <32 weeks of gestation with evolving or established BPD and reported that there was no significant difference in the mean oxygenation index between the two modes, but the mean alveolar–arterial gradient was better on NAVA. 108 NAVA can also be used as a non-invasive modality. Forty infants with a gestational age of 28–36 weeks requiring CPAP for respiratory distress were randomised to non-invasive NAVA or CPAP and the authors reported that, after 12 h of treatment, the mean FiO 2 requirement and need for invasive ventilation did not differ between the two groups.…”
Section: Neurally Adjusted Ventilator Assist (Nava)mentioning
confidence: 99%
“…Proportional assist ventilation (PAV) synchronizes pressure support with the patient's respiratory demand throughout the respiratory cycle. In a recent study, both PAV and NAVA were found to improve oxygenation when compared to conventional ventilation [29]. Still, important questions remain regarding the optimal level of support required for different neonatal respiratory problems.…”
Section: Synchronized Modes Of Imvmentioning
confidence: 99%
“…Even though extensively studied in animal models of different lung injuries, 22,23 the clinical application of PAV has only been evaluated in small cohorts of neonates during short periods focusing mainly on feasibility, 24,25 and less in prospective randomized controlled trials (RCTs). Clinical studies have shown short‐term benefits in neonates with acute respiratory distress syndrome (RDS) and evolving bronchopulmonary dysplasia (BPD) in terms of maintaining stable gas exchange and lower oxygen index at lower mean airway pressures (MAPs), compared to other modes of patient triggered ventilations 24–28 (Table 2), but no long term RCTs have been performed to evaluate outcomes such as the development of BPD and/or duration of mechanical ventilation. Both the facilitated spontaneous breathing and the lower MAP without compromised oxygenation or ventilation, suggest the possibility of using PAV to minimize ventilator induced lung injury in the early phase of life in extremely preterm infants, and later during the weaning of long term mechanically ventilated infants, applications that need future large controlled studies.…”
Section: Proportional Assist Ventilationmentioning
confidence: 99%
“…Additionally, periods of apnea and low EAdi activity were reported which necessitated back up ventilation and/or switching to other modes of ventilation in some infants 46 . In multiple small prospective cross‐over studies in infants with RDS or evolving BPD, NAVA has been shown to reduce the PIP, the fraction of inspired oxygen, and the work of breathing compared with other patient‐triggered ventilatory modes 28,46–55 (Table 4). In a multi‐center review of current clinical practice, NAVA was successful as a weaning mode of ventilation in infants with severe BPD 67% of the time 56 …”
Section: Neurally Adjusted Ventilatory Assistmentioning
confidence: 99%